2013
DOI: 10.1590/s1516-14392013005000148
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between density and anatomical structure of different species of Eucalyptus and identification of preservatives

Abstract: The species and density of Eucalyptus wood poles installed in the electrical network are useful parameters which must be considered when it is necessary to establish the service life of these structures. In this work, eucalyptus poles samples were collected and analyzed by scanning electron microscopy and energy dispersive spectroscopy (SEM/EDS). SEM image analysis showed that the lumen diameter average of fiber substantially is variable between the three species studied, in line with the wood density obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
2
0
3
Order By: Relevance
“…Undoubtedly, apparent density (ratio between mass and volume of a specimen at known moisture content) is the more easily obtained property (Dias and Lahr 2004;Abruzzi et al 2013;Sales and Lahr 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, apparent density (ratio between mass and volume of a specimen at known moisture content) is the more easily obtained property (Dias and Lahr 2004;Abruzzi et al 2013;Sales and Lahr 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Based on a mechanical analysis of a cell model, wherein the implications of the wall microstructure are taken into account, the authors show that the nature of its microstructure is crucial for explaining the shrinkage behavior of wood, with respect to its density. Abruzzi et al (2013) tried to relate density and anatomical characters for poles installed in the electrical network, of three Eucalyptus wood species. Image analysis showed that the mean lumen diameter of fibers varied expressively among the three species studied, in line with the wood density obtained in a laboratory, for poles with several years in service, as well as for unused poles.…”
Section: Introductionmentioning
confidence: 99%
“…Também, os resultados das propriedades físicas e mecânicas das espécies E. camaldulensis, E. alba, E. tereticornis também se mostraram próximos aos valores indicados por esta norma brasileira. Para as amostras de E. urophylla os resultados foram próximos dos valores da norma brasileira [14] e de outros estudos [20,[31][32][33][34][35][36][37][38]. Os valores determinados para a madeira de E. cloeziana ficaram próximos aos determinados por outros autores que estudaram as propriedades dessa espécie [39,40] e também quando comparados com os valores fornecidos pela norma brasileira [14].…”
Section: Resultsunclassified
“…Os resultados das características anatômicas das espécies deste trabalho, identificados na Tabela 5 e ilustrados a partir das Figuras 3 e 4, se encontram bastante próximos aos encontrados por outros autores [4,31,[33][34][35].…”
Section: Resultsunclassified
See 1 more Smart Citation